Strategic human resource development - Kandula, Srinivas R. (Srinivasa Rao), 1963- (New Delhi : Prentice-Hall of India, 2002)
Gives an analysis of the significance of the human resource development system in planning and implementing strategic responses, focusing on the alignment between strategic responses of organisations and human resource development in India's most valuable companies.
Includes bibliographical references (p. 329-376) and index
oif 11/11/14
Loan
Keywords: Personnel management -- India. Manpower planning -- India